MANAJEMEN SUMBER DAYA MANUSIA UNIVERSITAS KUTAI KARTANEGARA - Hasbi Sjamsir; Susilo; Achmad, Sjafruddin (BEduManagers Journal : Borneo Educational Management and Research Journal, 2021)
Education is a government effort to educate the people of Indonesia, as mandated in the opening of the Constitution 1945, Human resources education is an important factor for the success of an education that must be managed with the most, because with the management of human resources education this educational institution can produce quality graduatesto realize the quality of the college graduates are required a qualified HR lecturer through the management of human resources in the University of Kutai Kartanegara. Human Resource Management (MSDM) is managing recruitment, selection, awarding, efforts to maintain assessment and promotion of personnel to gain the welfare or sanction of the institutions. The research objectives are: (1) to describe the mechanism of HR recruitment. 2 To describe the efforts to increase HR capability. (3) to describe the HR career level. (4) to describe the welfare of human resources. (5) to describe the process of termination or termination of human resources at Kutai Kartanegara University. This method of research uses a case study method with a qualitative approach. Data collection techniques are conducted with; Interviews, observations, photography, and documentation. Data was analyzed by the interactive model Milles Huberman (1994), namely; Data collection, data reduction, display data, and conclusion. Data validity checks are conducted to test credibility, transferability, dependability and confirmability. The results of the study found (1) Therecruitment of resources lecturer in education and teaching is determined by the quality of lecturers. (2) Improving the resource capability of lecturers measured through performance. 3 Career Enhancement lecturer conducted with the implementation of college followers (4) Lecturers get guaranteed income, based on the performance report of lecturers (5) dismissal and sanctions system and award based monitoring, performance of lecturers using a written record system.